MANAJEMEN PEMBELAJARAN DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI DI MASA PANDEMI COVID-19 - Renawati Renawati; Erni Munastiwi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: This research was conducted to determine the learning management of children's cognitive development in the Covid-19 pandemic. The relationship between teachers and parents is very influential in early childhood, so cooperation is carried out between the two for learning management in cognitive early childhood in a pandemic because there are difficulties faced in the teaching and learning process at home. The research method used using qualitative methods. The results of the study indicate that there is learning management at Raden Sadjad's Angkasa Lanud Kindergarten for the success of early childhood teaching and learning in cognitive development during the current pandemic, namely: 1) Procedures for studying at home with parents, and 2) Principals and teachers. teachers make learning management for early childhood as attractive and efficient as online teaching and learning but does not eliminate the essence of improving children's cognitive development. Keywords: Learning Management; Cognitive; Early Childhood; Covid-19 Abstrak: Penelitian ini berdasarkan manajemen pembelajaran perkembangan kognitif anak dalam keadaan pandemi Covid-19. Manajemen pembelajaran dalam meningkatkan perkembangan kognitif anak usia dini sangat penting diterapkan terlebih saat pandemi Covid-19 sehingga dapat menjadi acuan untuk guru lain di Indonesia. Metode yang digunakan kualitatif deskriptif untuk menjelaskan hasil penelitian ke dalam data untuk di olah oleh peneliti. Lokasi penelitian dilakukan TK Angkasa Lanud raden Sadjad. Peneliti melakukan observasi, wawancara, dan dokumentasi dengan guru, kepala sekolah, dan orang tua di TK Angkasa Lanud Raden Sadjad. Hasil penelitian manajamen pembelajaran dalam meningkatkan perkembangan kongitif anak usia dini untuk jadi acuan ataupun arahan dalam guru memberikan bahan ajar pada anak saat belajar daring dilakukan. Kata kunci: Manajemen Pembelajaran; Kognitif; Anak Usia Dini; Covid-19